The Body and Space: real and imaginary - Musings on site-specific - Cavrell, Holly Elizabeth (Revista Brasileira de Estudos da Presença, 2023)
This article discusses a personal history of performances in which the focus is the body and its various relationships to space. Emphasis is given to the experiences of Cia. Domínio Público, a contemporary experimental research group, studies in site-specific and mural culture in Philadelphia. The discussion will traverse themes dealing with public art, site-specific performance, and intervention in public urban spaces. As the article explores new strategies for potentializing performative work in nontraditional venues, space is considered a partner in the creative process.